The Ties that Bind: Globalization, Filipino Citizens & the State - An Examination of Philippine Policies on the Welfare of Migrant Filipino Workers' Families - Ruiz Austria, Carolina S. (Review of Women's Studies, 2023)
This study is a preliminary inquiry into state policies for the welfare of Filipino migrant workers' families. While both permanent and temporary migrations are included in the study, most of the policies examined refer to the latter. The provisional character of migration for work by Filipinos is reflected in both the aspirations of Filipinos as well as ambiguous state policies which, belie that migration for labor is promoted by the state as a means to achieve economic growth. It asserts that part of the challenge in doing policy analysis on migrant families' welfare lies in considering how studies actively contribute to shaping discourse and framing which claims are legitimate or important.